Data Resource: Children and Family Court Advisory and Support Service (Cafcass) public family law administrative records in England - Bedston, Stuart; Pearson, Rachel; Jay, Matthew A; Broadhurst, Karen; Gilbert, Ruth; Wijlaars, Linda (International Journal of Population Data Science, 2020)
Introduction In England, in cases of child maltreatment or neglect, the state can intervene through the family court to remove them from their family home and place them in out-of-home care. The Children and Family Court Advisory and Support Service (Cafcass) collect and maintain administrative records of all public family law cases in England. While these records are primarily used to monitor and manage the case load of Cafcass teams across England, researchers have re-purposed this data for analysis to understand the drivers and outcomes of public family law intervention. Data contents The administrative dataset is a reflection of the cases Cafcass get involved with and the extent of their involvement. There are three main types of unit within the data: applicants (English local authorities), subjects (children) and parties (those with parental responsibility, typically biological mothers and fathers). As such, the data collected comprises information at the person-level (e.g. demographics of the children and adults), and information at the case-level (e.g. types of applications made, hearing dates and final legal outputs). Between 1 April 2007 and 31 March 2019, Cafcass have captured information on approximately172,100 public family law cases, involving 282,300 children, and 249,500 adults (of which 289,300 are recorded as biological parents). They record relations between adults and children making it possible to identify families. Additionally, Cafcass recording practices have improved over time, this has increased the availability of demographic information of all those involved, as well as child’s final legal outcome. Data access Researchers can apply to the Secure Anonymised Information Linkage Databank (SAIL) for access to the Cafcass pseudonymised administrative data extract, where it is refreshed bi-annually.